1992
DOI: 10.1111/j.1600-0838.1992.tb00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Periosteal transplantation in the treatment of osteochondritis dissecans

Abstract: transplantation in the treatment of osteochondritis dissecans. Scand J Med Sci Sports 1992: 2: 32-36.Osteochondritis dissecans in the femoral condyle of the knee in 3 patients was treated with periosteal transplantation. The cavities were curetted to cancellous bone and a tibial periosteal graft was lined to the excavation and fixed with human tissue glue (Tisseel R). By clinical and radiographic follow-up, we find this modality of treatment as a hopeful prospect in severe cases, though a demarcation of indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…A better understanding of the fate of cells within the fracture callus is necessary to assess the success of future cell‐based therapies. Several methods can be used to enhance bone repair in human, such as iliac crest bone grafts, cortical bone grafts, and periosteal grafts. (( 39–44)) Whether MSCs from bone marrow or other sources actually contribute to repair or support healing by providing factors inducing chondrogenesis or osteogenesis is not known. (( 45–48)) MSCs from the bone marrow have been shown to differentiate into osteoblasts and chondrocytes in vitro and are largely used in multiple tissue engineering approaches. (( 49–51)) Data show here that cells derived from bone marrow behave differently when they are recruited from their original niche because they mainly support osteogenesis in vivo. Although MSCs remain the most promising source of cells for human therapy, the mode of delivery and the fate of these cells once transplanted in vivo need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the fate of cells within the fracture callus is necessary to assess the success of future cell‐based therapies. Several methods can be used to enhance bone repair in human, such as iliac crest bone grafts, cortical bone grafts, and periosteal grafts. (( 39–44)) Whether MSCs from bone marrow or other sources actually contribute to repair or support healing by providing factors inducing chondrogenesis or osteogenesis is not known. (( 45–48)) MSCs from the bone marrow have been shown to differentiate into osteoblasts and chondrocytes in vitro and are largely used in multiple tissue engineering approaches. (( 49–51)) Data show here that cells derived from bone marrow behave differently when they are recruited from their original niche because they mainly support osteogenesis in vivo. Although MSCs remain the most promising source of cells for human therapy, the mode of delivery and the fate of these cells once transplanted in vivo need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies it has been shown that the periosteum has a chondrogenic potential [8,18,20], and a few clinical studies indicate a chondrogenic effect in hu- mans [1,5,9,10,14]. Recently, we reported excellent and good short-term (mean follow-up 27 months) results for 18 patients with deep cartilage lesions of the patella that were treated with autologous periosteum transplants fixed to the patellar subchondral bone bed with resorbable throughout sutures and fibrin glue (Tisseel) [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the few clinical reports on autologous periosteum transplantation, the fixation of the transplant varies. In some reports the transplant is sutured to the surrounding cartilage [2, 5, 10], while in others [1, 9,14] it is glued to the underlying bed with fibrin glue (Tisseel). With our method, the periosteum transplant is anchored to the bottom of the cartilage defect on the femoral condyle with the use of suture anchors and fibrin glue, to minimize the risk of loosening during rehabilitation training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ένα άλλο πεδίο που έχουν χρησιμοποιηθεί κλινικά τα περιοστικά μοσχεύματα είναι στη διαχωριστική οστεοχονδρίτιδα (109,125,195) . Η μεγαλύτερη σειρά είναι του Masden 163 και συνεργατών οι οποίοι αντιμετώπισαν 18 ασθενείς (11 άνδρες και 7 γυναίκες) με μέσο όριο ηλικίας τα 19 έτη.…”
Section: απόπτωσηςunclassified